When Darkness Meets Pressure: The Impact of Dark Triad Personality Traits on Work Stress among Employees in Indonesia's Collectivistic Cultures - Hasana, Yuniar; Nuzulia, Siti (Universitas Ahmad Dahlan, 2025)
Work stress is a prevalent issue across organizational settings, yet its relationship with dark personality traits remains underexplored in collectivistic culture contexts. This study investigates the impact of narcissism, Machiavellianism, and psychopathy on work-related stress among employees in Indonesia. This study employed a quantitative methodology and a cross-sectional design, with 255 employees in Indonesia selected via quota sampling. Data analysis was conducted using the General Linear Model (GLM). The findings indicate that psychopathy positively affects work stress, while Machiavellianism negatively impacts work stress. Narcissism does not have a significant effect on work stress. Marital status influences stress levels, with unmarried employees showing greater vulnerability to stress than those who are married. These results suggest that both Dark Triad personality traits and certain demographic factors contribute to variations in work stress. The study highlights the importance of considering personality and demographic characteristics in recruitment and employee support initiatives. Tailoring stress management strategies to individual profiles may enhance employee well-being and promote greater organizational effectiveness.